Is it worth investing in university education? The accounts of private higher education - Granados-González, Patricia; López-Moreno, Sergio; Moreno-Adalid, Ana M. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Statistics show that the net enrollment rate in undergraduate studies in Spain is increasing significantly. The aim of this research is to explore the evolution of the income statement and balance sheet of Spanish private university education companies. Using data published in the SABI database, the companies with the highest turnover and total assets have been analyzed. The main findings were an increase in turnover and profits of 40% and 20%, respectively. However, investment in assets has remained unchanged.